2017
DOI: 10.5301/ejo.5000942
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fibrinogen to Albumin Ratio in Ischemic Retinal Vein Occlusions

Abstract: The fibrinogen to albumin ratio is significantly associated with ischemic RVO. Instead of complicated and invasive methods, such as a retinal angiogram, the fibrinogen to albumin ratio could be a useful initial diagnostic test to predict ischemia in RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Accumulating studies have demonstrated that FAR, cooperating albumin and fibrinogen, is an important prognostic predictor in various cancer [16, 17]. Recently, Guclu et al indicated that an elevated FAR was significantly correlated with ischemic retinal vein occlusion [24]. In the study by Karahan et al, FAR was significantly related to SYNTAX Score in predicting the severity of CAD in patients with STEMI [25].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have demonstrated that FAR, cooperating albumin and fibrinogen, is an important prognostic predictor in various cancer [16, 17]. Recently, Guclu et al indicated that an elevated FAR was significantly correlated with ischemic retinal vein occlusion [24]. In the study by Karahan et al, FAR was significantly related to SYNTAX Score in predicting the severity of CAD in patients with STEMI [25].…”
Section: Discussionmentioning
confidence: 99%
“…Increased fibrinogen/albumin ratio was found to be associated with inflammation and oxidative stress in several diseases such as ankylosing spondylitis, esophageal squamous cell carcinoma, hepatocellular carcinoma, retinal vein occlusion, sensorineural hearing loss, ischemic stroke, and acute coronary syndrome. 2428…”
Section: Discussionmentioning
confidence: 99%
“…Increased fibrinogen/albumin ratio was found to be associated with inflammation and oxidative stress in several diseases such as ankylosing spondylitis, esophageal squamous cell carcinoma, hepatocellular carcinoma, retinal vein occlusion, sensorineural hearing loss, ischemic stroke, and acute coronary syndrome. [24][25][26][27][28] In the final stage of the coagulation cascade, fibrinogen is converted to fibrin by thrombin. Fibrin clot stops bleeding in the damaged vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described that coronary heart disease, such as myocardial infarction, because of its association with cardiovascular risk factors may be an independent risk factor of RVO [ 29 , 30 , 31 ]. Moreover, previous studies showed increased fibrinogen–albumin ratio defined as a marker of inflammation and disease severity in each patient with RVO or SSNHL [ 32 , 33 ]. One case study also reported the patients who suffered from central retinal vein occlusion and sudden deafness [ 34 ].…”
Section: Discussionmentioning
confidence: 99%